Environmental assessments for seabed impact and resilience from aquaculture: a case study in an intensive production area (Frøya, Norway) - Chun-Deng Wang; Dagfinn Breivik Skomsø; Yngvar Olsen (Frontiers in Marine Science, 2025)
Norway mandates protocols to manage salmon aquaculture’s impact on the seabed, with B-assessments for directly beneath the cages and C-assessments for the broader surrounding seabed with more chemical and biological variables. This study aimed to utilize existing data of C-assessments to synthesize findings on the spatial impacts of organic enrichment and associated biogeochemical processes. We analyzed a total of 27 assessments from 16 sites of commercial salmon farms from 2016 to 2022 at Sulfjorden on the coast of Central Norway. Each assessment measured both biological and chemical variables at the local impact zone (~30 meters from sea cages), intermediate zone (30–500 m from sea cages), and the edge of intermediate zone (~ 500m from sea cages). The main finding was that C-assessments can detect subtle impacts of organic enrichment, even when B-assessments rate the benthic environment beneath the farms as very good. The levels of Carbon (C), Nitrogen (N), Zinc (Zn), Copper (Cu), and the biodiversity of benthic macrofauna varied significantly in the different zones (p< 0.05). Chemical variables showed the highest influence in the local impact zone, with levels decreasing promptly with distance from the cages. At the boundary of the intermediate zone, the levels were no longer different from those at the reference site. Furthermore, chemical support variables were negatively correlated with benthic biodiversity (all p< 0.05), supporting that these variables can reveal subtle changes and spatial variations in the state of the benthic ecosystem. Thus, we suggest that C-assessments are a reliable approach for detecting benthic changes beyond the immediate impact zone while also confirming whether these effects are limited to areas near the facility. While the C-assessment primarily relies on benthic fauna analyses to evaluate environmental conditions, our findings suggest that supporting variables play a crucial role in predicting the spatial dynamics of organic enrichment from cage aquaculture.